ADOLESCENT STUDENTS' ATTITUDES TOWARDS SEXUALITY: THE CONSTRUCTION AND VALIDATION OF A SCALE - Barros,Teresa Madalena Kraus Brincheiro Hüttel (2021)
ABSTRACT Objective: To construct a scale of adolescents' attitudes towards sexuality and to determine their psychometric characteristics. Methods: Methodological study conducted with 394 students from the 8th to 12th grades of a school in central Portugal. They answered a questionnaire consisting of the Adolescent Students' Attitude Scale for Sexuality (E3AS) and socio-demographic and academic data. The project received a favorable opinion from the National Data Protection Commission (authorization No. 10421/2017). Construct validity analysis was performed through exploratory factor analysis and internal consistency was performed through Cronbach's alpha. A maximum error probability of 5% was considered. Results: The mean age of the sample was 14.9±1.4 years, with 53.3% being female. The instrument consisted of 34 items distributed into five factors: F1. Family planning and sex education (α=0.826); F2. First sexual relationship (α=0.819); F3. Violation of sexual rights and who to turn to in the event of unplanned pregnancies (α=0.695); F4. Gender expression and identity (α=0.542), and F5. Unplanned pregnancy and parenting (α= 0.761), with a total alpha value of 0.766, accounting for 45.3% of total variance. Conclusions: The psychometric adequacy of the E3AS for the Portuguese population allows us to affirm that it is a valid and reliable instrument that can be used in future studies to assess the attitudes of adolescent students towards sexuality.